ANALISIS FRAMING MODEL ROBERT N. ENTMAN DALAM REPRESENTASI PUBLIK FIGUR POLITIK: EPISODE 'DOSA-DOSA ANIES' DI PROGRAM 'KICK ANDY' METRO TV - Widyaya, Ismoko; Setiawan, Wiji (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This research analyzes the episode "Dosa-Dosa Anies" from the show "Kick Andy" on Metro TV which is an exclusive interview with former Governor of DKI Jakarta Anies Baswedan who is a presidential candidate in the 2024 election. This analysis uses qualitative methods and a framework from Robert N. Entman to understand media through interviews featuring Anies Baswedan on various related issues. The results of this analysis show that this episode succeeded in identifying the main problems related to Anies Baswedan, explaining the causes of the problems from various points of view, as well as raising ethical problems that had occurred and suggesting improvements to a policy. These findings highlight the importance of the media in shaping perceptions and evaluations of political figures, especially in the run-up to general elections. This research helps the public understand the role of the media in the context of politics and democracy, and emphasizes the importance of integrity and ethics in mass communication. Analysis of coverage like this is important to ensure accurate and balanced information about potential leaders, which is important for maintaining media integrity and democracy in Indonesia.